1969
DOI: 10.1126/science.164.3875.84
|View full text |Cite
|
Sign up to set email alerts
|

Honey Bee Recruitment to Food Sources: Olfaction or Language?

Abstract: Honey bee recruits locate food sources by olfaction and not by use of distance and direction information contained in the recruitment dance. Recruitment efficiency increases as odor of the food source accumulates in the hive, from hour to hour and from day to day. Flight patterns, landing patterns, bee odor, and Nassanoff secretion apparently do not aid in recruitment of bees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
1
2

Year Published

1977
1977
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(57 citation statements)
references
References 17 publications
1
53
1
2
Order By: Relevance
“…An alternative hypothesis (292) proposes that, although the dance undoubtedly bears information about the distance and direction of the food source, this information is not used by the recruits to find the food. Rather, they home in on the food source by following scent cues acquired from the nectar or pollen that she has brought back, or by following the dancer herself to the food, using visual or olfactory cues (293). According to this view, the waggle dance that is orchestrated by a bee is simply a device to gather the attention of potential recruits, to convey food samples to them, and to induce them to follow her, or the scent of the food, to the destination.…”
Section: Estimating Distance Flown: Thementioning
confidence: 99%
“…An alternative hypothesis (292) proposes that, although the dance undoubtedly bears information about the distance and direction of the food source, this information is not used by the recruits to find the food. Rather, they home in on the food source by following scent cues acquired from the nectar or pollen that she has brought back, or by following the dancer herself to the food, using visual or olfactory cues (293). According to this view, the waggle dance that is orchestrated by a bee is simply a device to gather the attention of potential recruits, to convey food samples to them, and to induce them to follow her, or the scent of the food, to the destination.…”
Section: Estimating Distance Flown: Thementioning
confidence: 99%
“…To optimize foraging, insects like honeybees learn to discriminate floral olfactory cues associated with a valuable reward from those that do not predict food (Menzel, 1999). However, odors are not learned exclusively in the field but also inside the nests, for example when the intake of scented food from foragers lead to biased foraging preferences of their nest mates in the field (e.g., for honeybees: von Frisch, 1923;Wenner et al, 1969; for bumblebees: Dornhaus and Chittka, 1999; for yellow jacket: Jandt and Jeanne, 2005; for ants: Roces, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Um das Sammelverhalten zu optimieren, lernen Honigbienen sowohl an der Sammelstelle als auch innerhalb des Volkes olfaktorische Blüteneigenschaften mit einer Belohnung zu assoziieren (z.B. von Frisch, 1923;Wenner et al, 1969). In neueren Untersuchungen konnten wir zeigen, dass assoziative Lernereignisse wie die obengenannten zur Ausbildung eines olfaktorischen Gedächtnisses führen, das dann wiederum dazu genutzt wird, den gelernten Duft in der Umgebung aufzufinden (Arenas et al, 2007 Apis mellifera / Honigbienen / Geruchslernen / Langzeitgedächtnis / Futterwahl…”
unclassified
“…The ability to use olfactory information acquired in various contexts during subsequent orientation tasks might contribute to the enhancement of orientation performance. Reporting that flower volatiles, carried by 3732 returning foragers from the sites they have recently visited, could be used by the recruits to search for food, von Frisch (1967) and Wenner et al (1969) were the first to demonstrate that olfactory information acquired in the hive can be used in an orientation context. Since then, some studies have shown that bees are able to transfer information from a foraging situation to an associative context (Gerber et al, 1996) and from an associative context to a walking orientation response in an olfactometer (Backchine et al, 1992;Sandoz et al, 2000).…”
mentioning
confidence: 99%